Pengembangan Aplikasi Mobile Untuk Mencari dan Memberikan Pertolongan Terhadap Masalah Pada Kendaraan Berdasarkan Lokasi Terdekat - Rizky Kharisma; Herman Tolle; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Amount of motor vehicles are increase every year, that can increase motor vehicle's problems that occur such as tires leak, run out of gasoline or strike. The problem occurs when the vehicle makes people will need help from others to overcome it because of the human nature that is a social creature. With the human nature that has prosocial behavior causes the emergence of crowdsourcing phenomenon to mobilize its ability in overcoming a thing or help solve the problem. Crowdsourcing is a concept that allows a group or individual to collaboratively do a job or doing something given. With the increasingly high development of smartphones, especially users of android system operations, enabling the search for help can use the concept of crowdsourcing to throw open announcements about help search and take advantage of GPS features on existing smartphones so they can search for other people around the site to find the nearest help giver. Based on validation test, this application has fulfilled the 7 functional requirements. While the results of usability testing based on usefulness, easy to use, easy to learn and satisfaction showed a score reaching an average of 90,08% which can be concluded that the search application and provision of assistance on vehicle problems can be accepted and easily used.